PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMP NEGERI 2 POPAYATO BARAT KECAMATAN POPAYATO BARAT KABUPATEN POHUWATO - Olivia Olivia; Abdulrahim Maruwae; Yulianti Toralawe; Melizubaida Mahmud; Agil Bahsoan (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Educators are crucial in developing high-quality human resources. They serve not only as teachers but also as mentors and educators. Teachers must demonstrate professionalism, adaptability to change, and the ability to provide high-quality learning services in their roles. The purpose of this research is to identify the efforts made by the principal to improve teacher performance as well as the challenges faced at SMP Negeri 2 Popayato Barat. This study uses a qualitative descriptive approach. The data sources are teachers who serve as informants through in-depth interviews guided by an interview protocol. The data analysis technique involves data reduction, data presentation, and drawing conclusions. The results show that the principal’s efforts to improve teacher performance are realized through a democratic leadership style, supervision of learning administration, providing motivation during meetings, verbal appreciation, and monitoring teacher discipline. However, the principal’s role is still not optimal due to infrequent academic supervision, insufficient communication, lack of firmness in rules, and limited appreciation mostly in the form of verbal support.